Synthesis and magnetic properties of a nitrogen-containing fullerene dimer - Hörmann, F; Hirsch, A; Porfyrakis, K; Briggs, G (2011)
We report here on the two-step synthesis of fullerene dimer 3 from monomer 2. The structures were confirmed by MALDI mass spectrometry, UV/Vis, FTIR, 1H NMR, and 13C NMR spectroscopy. The magnetic properties of the analogous species of dimer 3, N@C140H24O 12, were studied by continuous-wave electron-spin resonance (CW-EPR), indicating that the functionalization introduces a permanent zero-field splitting (ZFS) D = 8.6 MHz and E = 0.45 MHz. The same synthetic procedure could be used to produce a 14N-15N dimer enabling spin resonance experiments that could demonstrate entanglement between electron spins. N@C60-containing dimers have been proposed as quantum bits (qubits) for a quantum information processing device. Herein, we demonstrate the feasibility of synthesizing such dimeric systems, while at the same time retaining the extraordinary paramagnetic character of N@C60. © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.